Generalized fractional differential equations and inclusions equipped with nonlocal generalized fractional integral boundary conditions - Ntouyas, Sotiris K.; Ahmad, Bashir; Alghanmi, Madeaha; Alsaedi, Ahmed (Topological Methods in Nonlinear Analysis, 2019)
In this paper, we establish sufficient criteria for the existence of solutions for generalized fractional differential equations and inclusions supplemented with generalized fractional integral boundary conditions. We make use of the standard fixed point theorems for single-valued and multivalued maps to obtain the desired results, which are well illustrated with the aid of examples.